Measurement of spin correlation in t(t)over-bar production using dilepton final states - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (Elsevier B.V., 2011)
We measure the correlation between the spin of the top quark and the spin of the anti-top quark in t (t) over bar -> W(+)bW(-)(b) over bar -> l(+)vbl(-) (v) over bar(b) over bar final states produced in p (p) over bar collisions at a center of mass energy root s = 1.96 TeV, where l is an electron or muon. The data correspond to an integrated luminosity of 5.4 fb(-1) and were collected with the D0 detector at the Fermilab Tevatron collider. The correlation is extracted from the angles of the two leptons in the t and (t) over bar rest frames, yielding a correlation strength C = 0.10(-0.45)(+0.45). in agreement with the NLO QCD prediction within two standard deviations, but also in agreement with the no correlation hypothesis. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Top quark; Spin; QCD